CLINICAL PROFILE OF CHILDREN WITH FEBRILE SEIZURE IN A TEACHING HOSPITAL - PRIYANISHABEN, DHODI; KHAN, ZUBAIR; patil, Pushparaj (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: To find out the clinical feature and outcomes of febrile seizures. Methods: After written informed consent, detailed clinical history of each patient including a time of presentation, the onset of fever and associated symptoms, data regarding demographic details, duration and type of seizure, history of seizures, and antiepileptic drug, repetition of seizure within 24 h, past history of seizures, birth history, family history was taken and entered in predesigned pro forma. Collected data were checked and verified for correctness and accuracy, which was then analyzed using statistical methods. Results: In the present study male-to-female ratio was 1.75:1. The maximum number (82.5%) of patients lacked a family history of febrile seizure, while 17.5% of patients had a positive family history of FS. 70% of the pediatric patients had upper respiratory tract infection. The maximum number of patients had simple febrile seizures, which are 81.25%, whereas 18.75% of patients had complex febrile seizures. The majority (73.75%) of patients in the present study had anemia. WBC count >11×109/L was found in 45 patients out of 80 (56.25%), and WBC count<4.5×109/L was found in 6 out of 80 (7.5%). Conclusion: Majority of patients with febrile seizures presented at a younger age which might represent the vulnerability of the developing brain to fever. As all the patients were discharged without any complication, so this study further adds to the knowledge of the benign nature of this disease.